The Type IV Secretion System of ICEAfe1: Formation of a Conjugative Pilus in Acidithiobacillus ferrooxidans - Flores-Ríos, Rodrigo; Moya-Beltrán, Ana; Pareja-Barrueto, Claudia; Arenas-Salinas, Mauricio; Valenzuela, Sebastián; Orellana, Omar; Quatrini, Raquel (Frontiers in Microbiology, 2019)
The dispersal of mobile genetic elements and their gene cargo relies on type IV secretion systems (T4SS). In this work the ICEAfe1 Tra type T4SS nanomachine, encoded in the publically available genome of Acidithiobacillus ferrooxidans ATCC 23270, was characterized in terms of its organization, conservation, expression and mating bridge formation. Twenty-one conjugative genes grouped in four genetic clusters encode the ICEAfe1 T4SS, containing all indispensable functions for the formation and stabilization of the pili, and for DNA processing. The clusters organization resembles that of other mobile genetic elements (such as plasmids and integrative and conjugative elements, ICEs). Sequence conservation, genetic organization and distribution of the tra system in the genomes of other sequenced Acidithiobacillus spp. suggests that the ICEAfe1 T4SS could mediate the lateral gene transfer between related bacteria. All ICEAfe1 T4SS genes are transcriptionally active and expressed from four independent operons. The transcriptional levels of selected marker genes increase in response to Mitomycin C treatment, a DNA damage elicitor that has acknowledged stimulatory effects on excision rates and gene expression of others ICEs, including ICEAfe1. Using a tailored-made pilin-antiserum against ICEAfe1 T4SS TraA pilin and epifluorescence microscopy, presence of the conjugative pili on A. ferrooxidans cell surface could be demonstrated. Also, immunodetection assays, by immunogold, allowed the identification of pili-like extracellular structures. All together, the results obtained in this work demonstrate that the ICEAfe1 T4SS is phylogenetically conserved within the taxon, is expressed at mRNA and protein levels in vivo in the A. ferrooxidans type strain, and produces a pili-like structure of extracellular and intercellular localization in this model acidophile, supporting its functionality. Additional efforts will be required to prove conjugation of the ICEAfe1 or parts of this element through the cognate T4SS.